Identity à la Wilde (Knjiženstvo, journal for studies in literature, gender and culture, 2024)
This paper discusses Oscar Wildeʼs play The Importance of Being Ernest in the context of developing the individual social and personal identity. Through a comparative analysis of dramatic relations, characterised by ambivalence and a dynamic of the “masculine” and the “feminine”, the paper seeks to establish a relationship to contemporary society, Western culture, and ideas of identity, sexuality, gender, and art. The analysis primarily focuses on the notion of form, both in the context of artistic expression and the expression of personal identity (i.e. truth), as well as its relationship to the idea of pleasure. This is based on observations concerning the surprising topicality of Ernest’s themes in the contemporary social context. Theoretical and methodological support is found in the prominent philosophical and feminist critical thought of the 20th and 21st centuries which significantly influenced the rethinking of Western society and the individual in it. In a broader sense, the said critical thought involves Susan Sontag and Judith Butler’s reflection on beauty, gender, and morality. In a narrower sense, the analysis draws on Luce Irigaray and Michael Foucault’s conclusions about language, gender, sexuality, and (contemporary) social practices. This is briefly laid out in Chapter 1 (“Introduction”). The drama analysis unravels in six points, starting with considering language as an artistic and a social means of expression in Chapter 2 (“To play with wonderful expression”). Chapter 2 briefly examines the connection of beauty with the notions of deceit, vanity, superficiality and thoughtlessness in the Western social subconscious, and its relationship to Wilde’s general poetics. The analysis continues, reflecting on the significance of language and form (Chapter 3: “The absurd importance of language forms”) but also their oppressive qualities, and the potentially repressive and complex relationship between the notions of form and pleasure, a relationship expressed through food symbolism in Wilde’s play (Chapter 4: “The oppressive authority of language forms”). Chapters 3 and 4 explore Oscar Wilde’s take on Victorian social conventions and practices, and the repercussions of language in social and artistic communication. While Chapter 3 comments on the general layout of Wilde’s play and the way its characters interact, Chapter 4 draws on Foucault and Irigaray’s views and insights into the dynamics between institutional power, public morality, and gender (in)equality, to reflect on these concepts concerning the notion of pleasure. Chapter 5 (“Formal repression of pleasure”) continues to explore Wilde’s idea of pleasure, as represented in Earnest, as well as its relationship with utility and what is socially perceived as “masculine” or “feminine” aspects of an individual. Chapter 6 (“An abundance of double exposures”) suggests that everything in The Importance of Being Earnest is doubly exposed and has the potential to create new layers of double exposures. Finally, in Chapter 7 (“Formal pleasure and pleasurable formality – an ‘ideal’ in the age of ideals?”), the analysis concludes with an overview of an ambivalent, i.e., a polyvalent dramatic constellation that leads to the individual creation of a unique, fluid identity (“Ernest”), which comprises both “masculine” and “feminine” aspects and their infinite combinations. In this identity – what might be called identity à la Wilde – the formal and the pleasurable are truly, earnestly intertwined. Chapter 8 (“Conclusion”) further highlights this claim, concluding that the importance of being earnest is the importance of recognising different aspects and accepting social and individual identities as inherently polyvalent phenomena, ever dynamic, fluid, and evolving.
Keywords: Oscar Wilde; identity; sexuality; drama; Ernest